Combination of Mollase and Glucose as Substrate for The Production of Biosurfactant by Bacillus subtilis BK7.1 - Danang Susetyo Rizky; Retnaningrum Endah; Wilopo Wahyu; Hadisusanto Suwarno; Salamun; Ni’matuzahroh; Fatimah (BIO Web of Conferences, 2024)
Biosurfactant is a secondary metabolite which has properties and structures such as surfactants that are able to decrease surface tension water and cause microsolubilization or emulsification. Biosurfactants are active compounds that are produced at the microbial cell surface or excreted especially Bacillus. Previous research reported that B. subtilis BK7.1 had ability to form biosurfactant. In this study, B. subtilis BK7.1 produced biosurfactant using a combination of molasse and glucose as a carbon source. The purpose of study was characterized biosurfactant from B. subtilis BK7.1 by counting the emulsification index and the surface tension of supernatant, calculating (CMC) value, and examining stability of biosurfactant. B. subtilis BK7.1 could produce the biosurfactant from molasse and glucose with CMC value was about 4 g/L. Biosurfactant of B. subtilis BK7.1 could reduce the surface tension of medium from 54.68 to 49.2 mN/m, emulsify kerosene around 15.8%, had temperature stability in the range of 27⁰C to 45⁰C, and had stability at pH 6. This study showed that the use of molasses waste combined with glucose in biosurfactant production was very efficient and had potential for further applications.